Kemampuan Literasi Digital Mahasiswa dan Peran Vital Perpustakaan Perguruan Tinggi dalam Peningkatannya; Studi Kasus IAIN Langsa - Mukhtarullah, Millatina; Agniya, Ursa (UPT Perpustakaan UIN Alauddin Makassar, 2025)
The development of information and communication technology has resulted in an abundant information landscape, but students often lack critical and ethical skills in filtering information, making them vulnerable to disinformation. They have difficulty distinguishing valid sources and using effective search tools. This study aims to examine the role of the IAIN Langsa Library in improving students' digital literacy through programs, services, and resources, and to examine the relationship between students' digital literacy and the library's efforts to improve the ability to search, evaluate, and manage digital information for academic purposes. The research method uses a literature study with a qualitative-descriptive approach, involving the collection and analysis of relevant scientific sources. The results show that the IAIN Langsa Library strives to improve students' digital literacy in three main categories. First, through programs such as user education to provide effective access, evaluation, and utilization of digital information; digital skills workshops and training that provide insight into digital trends; and digital literacy competitions to motivate creativity and technical skills. Second, various services include on-site reading, references, scientific papers, circulation, library kids' corners, GLAC, and online administration for convenience, such as free libraries and thesis receipts. Third, adequate resources in the form of print and digital collections, access to e-resources, and e-learning platforms for independent and flexible learning. Research has found a positive and significant relationship between students' digital literacy skills and library efforts.